Narrative Rhetoric in Expert Reports:: A Case Study - Baldwin, Clive (Narrative Matters, 2011)
Rhetoric within narratives has been the focus of attention for several well-known scholars in the field of literary criticism. While other forms of writing, such as professional reports, have been analysed through the lens of narrative, the rhetoric therein has received little attention. Although the official position is that UK child protection proceedings are inquisitorial and evidence-based, it is possible to identify rhetorical practices in both narratives of professional reports and the court proceedings. Drawing on Aristotle’s Rhetoric, I will analyse rhetorically the expert pediatric reports presented in a case of alleged Munchausen syndrome by proxy, focusing in particular on ethos and pathos. In so doing, I will seek to illustrate how rhetoric permeates child protection proceedings and indicate how rhetorical analysis might aid the evaluation of evidence and testimony.